Securities Crowdfunding (SCF) System As An Alternative To MSMEs Funding In East Java - Dian Eka Pratiwi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
Fintech has a significant impact on the ease of society in meeting their financial needs. Fintech through Securities Crowdfunding can also be an alternative to new funding by expanding access to capital for MSMEs and start-ups. With the advancement of technology and information systems that are present in the form of Securities Crowdfunding. Making it easier for MSMEs to obtain funding, in addition to simpler requirements, this Securities Crowdfunding platform can be accessed through gadgets or computer devices with the help of the internet anywhere and anytime. The purpose of this paper is not only to explain the concept of the Securities Crowdfunding system in Indonesia, but also to analyze the potential of the Securities Crowdfunding,especially in East Java.